Implementasi Teori Refinement pada Pengkomposisian Soal pada Game berbasis Web Semantik - Mohammad Yani (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
This paper explores the implementation of refinement theory in questions composition for semantic webbased Arabic Learning game. The refinement theory is used to assess the degree of sophistication of the game, while semantic web is a concept that improves web document into web data. In this paper, a simple ontology about game questions composition is developed by implementing refinement theory to distinguish the difficulty of each level. This, hopefully, will motivate players to continue playing their game into the next level. This research conclude that the relation between value of R and question complexity is a negative correlation. The higher the value of R, the lower the question complexity.